RHEOLOGICAL CHARACTERIZATION OF LOW-CALORIE JELLIES AND MARMALADES MODEL SOLUTION - MOURA, SÍLVIA CRISTINA S. R. DE; VISSOTTO, FERNANDA Z.; DE ALMEIDA, MARIA EUGENIA M.; FEFIM, DJANE A. (Revista Brasileira de Engenharia de Biossistemas, 2008)
Gums mixtures has attracted the attention of a growing number of researchers due to the expectationof greater flexibility in its mechanisms and structural and rheological properties in relation to purefood gums. The study purpose was to perform eleven solution models of low-calorie marmaladesand jellies using various hydrocolloids, and to compare their rheological characteristics. It wasobserved that viscosity decreased with increasing temperature, adjusting to Arrhenius model. TheHerschel-Bulkley was the rheological model that best fit to data, with n <1, pseudoplastic fluid.Change in viscosity with time was evaluated, and most of model solutions showed thixotropicbehavior.